2018
DOI: 10.36497/jri.v38i3.2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile and Treatment Evaluation of Rifampicin-Resistant and Multidrug-Resistant Tuberculosis Patients at Dr. Kanujoso Djatiwibowo Public Hospital, Balikpapan

Abstract: Background: Rifampicin-resistant (RR-TB) and multidrug-resistant tuberculosis (MDR-TB) remains a major health problem worldwide and in Indonesia also become a challenge in total eradication of tuberculosis. Dr. Kanujoso Djatiwibowo Public Hospital (RSKD) Balikpapan is one of the two referral hospitals in East Kalimantan for evaluation and initiation of MDR-TB treatment. The objective of this study is to evaluate clinical profile and treatment of RR-TB and MDR-TB patients at RSKD. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 7 publications
2
4
1
2
Order By: Relevance
“…Based on Table 1, from 178 DR TB patients, 34.2% RR TB patients and 65.8% MDR TB patients were found. This result differed from studies by Tirtana & Musrichan (2011) and Adiwinata et al (2018), which stated that monoresistance to rifampicin was the most common resistance pattern. It might be because isoniazid and rifampicin are the first-line active drugs in TB therapy.…”
Section: Characteristics Of Drug-resistant Tb Patientscontrasting
confidence: 99%
“…Based on Table 1, from 178 DR TB patients, 34.2% RR TB patients and 65.8% MDR TB patients were found. This result differed from studies by Tirtana & Musrichan (2011) and Adiwinata et al (2018), which stated that monoresistance to rifampicin was the most common resistance pattern. It might be because isoniazid and rifampicin are the first-line active drugs in TB therapy.…”
Section: Characteristics Of Drug-resistant Tb Patientscontrasting
confidence: 99%
“…Moreover, other intervention such as counselling, health education, as well as adequate support was mandatory in patients with MDR-TB. It is expected to improve the management and to limit the drop out case (Adiwinata, Rasidi, Marpaung, Timur, & Timur, 2018). An effective early diagnosis and pharmacotherapy would be key to reduce failure of TB treatment (Bhatt, Chopra, & Vashisht, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…9 History of previous TB treatment such as failed category 1 TB cases, relapsed TB cases, and dropped out of treatment are groups at high risk of developing resistance. 10 Comorbidity can also be a risk factor for anti-TB drug resistance associated with decreased immunity. 11 Based on the differences in first-line anti-TB drug resistance patterns in various places and the previously mentioned facts, there are several opportunities in the development of studies on first-line anti-TB drug resistance patterns in Indonesia.…”
Section: Original Articlementioning
confidence: 99%
“…19 Another study in Balikpapan, Indonesia also showed that the dominant pattern was HR in 5 of 15 patients (33.3%) and followed by isoniazid, rifampicin, pyrazinamide, ethambutol (HRZE) in 2 patients (13.3%). 10 Based on several studies in Indonesia, the dominant pattern of first-line anti-TB drug resistance in Indonesia is HR. 10,18,19 This may be due to the fact that isoniazid and rifampicin are the first-line active drugs in TB therapy.…”
Section: First-line Anti-tuberculosis Drug Resistance Patternmentioning
confidence: 99%
See 1 more Smart Citation